Association of PIN3 16-bp duplication polymorphism of TP53 with breast cancer risk in Mali and a meta-analysis - Brehima Diakite; Yaya Kassogue; Guimogo Dolo; Oumar Kassogue; Mamadou Lassine Keita; Brian Joyce; Erin Neuschler; Jun Wang; Jonah Musa; Cheick Bougari Traore; Bakarou Kamate; Etienne Dembele; et al. (BMC, 2020)
Abstract Background Breast cancer, the most common tumor in women in Mali and worldwide has been linked to several risk factors, including genetic factors, such as the PIN3 16-bp duplication polymorphism of TP53. The aim of our study was to evaluate the role of the PIN3 16-bp duplication polymorphism in the susceptibility to breast cancer in the Malian population and to perform a meta-analysis to better understand the correlation with data from other populations. Methods We analyzed the PIN3 16-bp duplication polymorphism in blood samples of 60 Malian women with breast cancer and 60 healthy Malian women using PCR. In addition, we performed a meta-analysis of case-control study data from international databases, including Pubmed, Harvard University Library, Genetics Medical Literature Database, Genesis Library and Web of Science. Overall, odds ratio (OR) with 95% CI from fixed and random effects models were determined. Inconsistency was used to assess heterogeneity between studies and publication bias was estimated using the funnel plot. Results In the studied Malian patients, a significant association of PIN3 16-bp duplication polymorphism with breast cancer risk was observed in dominant (A1A2 + A2A2 vs. A1A1: OR = 2.26, CI 95% = 1.08-4.73; P = 0.02) and additive (A2 vs. A1: OR = 1.87, CI 95% = 1.05-3.33; P = 0.03) models, but not in the recessive model (P = 0.38). In the meta-analysis, nineteen (19) articles were included with a total of 6018 disease cases and 4456 controls. Except for the dominant model (P = 0.15), an increased risk of breast cancer was detected with the recessive (OR = 1.46, 95% CI = 1.15-1.85; P = 0.002) and additive (OR = 1.11, 95% CI = 1.02-1.19; P = 0.01) models. Conclusion The case-control study showed that PIN3 16-bp duplication polymorphism of TP53 is a significant risk factor for breast cancer in Malian women. These findings are supported by data from the meta-analysis carried out on different ethnic groups around the world.